A Competing Risk Analysis Model to Determine the Prognostic Value of Isolated Tumor Cells in Axillary Lymph Nodes for T1N0M0 Breast Cancer Patients Based on the Surveillance, Epidemiology, and End Results Database - Li, Yijun; Zhang, Huimin; Zhang, Wei; Ren, Yu; Qiao, Yan; Li, Kunlong; Chen, Heyan; Pu, Shengyu; He, Jianjun; Zhou, Can (Frontiers in Oncology, 2020)
Introduction: Knowledge of the association between isolated tumor cells (ITCs) in breast cancer patients and the outcome is very limited. We aimed to determine the prognostic value of axillary lymph node ITCs for T1N0M0 female breast cancer (FBC) patients. Methods: Data for T1N0M0 FBC patients staged ITCs negative [pN0(i-)] and positive [pN0(i+)] were extracted from the Surveillance, Epidemiology, and End Results database from 2004 to 2015. Prognostic predictors were identified by Kaplan–Meier analysis, competing risk model and Fine-Gray multivariable regression model. Results: A total of 94599 subjects were included, 88632 of whom were staged at pN0(i-) and 5967 were pN0(i+). Patients staged pN0(i+) had worse breast cancer specific survival (BCSS) (HR: 1.298, 95% CI=1.069-1.576, P=0.003) and higher breast cancer specific death (BCSD) rate (Gray’s test, P=0.002) than pN0(i-) group. In the Fine-Gray multivariable regression analysis, pN0(i+) group had higher BCSD rate (HR:1.321,95% CI=1.109-1.575, P= 0.002) than pN0(i-) group. In subgroup analyses, no significant difference in BCSD was shown between chemotherapy and non-chemotherapy subgroup (Gray’s test, P=0.069) or radiotherapy and non-radiotherapy subgroup (Gray’s test, P=0.096). Conclusion: ITCs was independently related to the increase of BCSD rate and could be identified as a reliable survival predictor for T1N0M0 FBC patients.